1998
DOI: 10.1097/00000658-199805000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Service Cost

Abstract: Identification of the true cost centers and directed attending surgeon involvement are essential to the development and implementation of a successful cost-reduction process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 19 publications
0
23
0
2
Order By: Relevance
“…Medical care costs have most often been associated with lengths of hospitalization [6, 23± 26]. Other commonly identified factors include the effectiveness of treatment protocols, illness or injury severity, and cost-containment measures applied by third-party payers [18,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Medical care costs have most often been associated with lengths of hospitalization [6, 23± 26]. Other commonly identified factors include the effectiveness of treatment protocols, illness or injury severity, and cost-containment measures applied by third-party payers [18,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, the true financial impact of these strategies remains largely unknown. Our group has previously reported a 25% reduction in variable direct cost per patient, 7 but the exact impact of our interventions on total costs and the hospital's bottom line has yet to be ascertained. Our analysis revealed that variable direct costs account for approximately 35% of total patient care costs.…”
Section: Discussionmentioning
confidence: 95%
“…The influence of the physician regarding cost reduction in a hospital is extremely limited and may lie between 25 and 35% of variable direct costs. The best cost reductions in a 1-year survey were achieved in pharmacy (57%), nursing (24%), and emergency (36%) [41]. Other estimates of a hospital overhead of 84% [14] have been found to be way beyond the physician's immediate control [42].…”
Section: Cost Calculations On the Basis Of A Trauma Registrymentioning
confidence: 98%